EXTRACTIVISM: THE DISPUTE OVER CONTROL OF NATURE AND SOCIETY IN MEXICO - Ocampo-Ledesma, Jorge Gustavo (2025)
Extractivism, derived from capitalist expansion, expresses the plundering of dominated territories. It is based on the idea that nature is an inexhaustible source of resources for progress. The problem lies in the magnitude, scale, and objectives of this activity, which are based on different worldviews. The objective of this work is to explain the fundamentals of extractivism, its dynamics and its relationship with capitalism, as well as its impact on the rural situation in Mexico. The information was obtained from bibliographic and documentary sources, integrating the approaches of social history and the long duration. To understand it, it is necessary to study the evolution of energy sources for human life and production: firewood, coal, gas, and oil. There is a relationship between the forms it takes and the stages of capital accumulation and domination. In this way, it has maintained its characteristics, although it has changed over time. Neocolonialism, which was already present in the colonial era, takes on new forms, such as neo-extractivism, which generates new wealth, now under a neoliberal economic model.